Percentage Attacks of Plutella xylostella and Parasitization of the Parasitoid Diadegma semiclausum on Cabbage in Kintamani District - Dicky Marsadi; Dewa Ayu Ari Febriyanti (Journal of Sustainable Development Science, 2024)
Cabbage plants are one of the horticultural commodities that many farmers cultivate in Indonesia because they have economic value, because apart from being able to meet domestic needs, cabbage also has the opportunity to become an export commodity. This study aims to determine the percentage of attacks by the cabbage leaf caterpillar Plutella xylostella and the level of parasitization of the parasitoid Diadegma semiclausum in Kintamani District. This research was carried out in Sekaan Village and Kedisan Village. The research method uses a survey method. Sampling of cabbage plants in the field was carried out diagonally so that 5 sample points were obtained, 10 plants were observed at each sample point. The research results showed that the percentage of P. xylostella pest attacks in Sekaan Village and Kedisan Village ranged from 12% to 28%. The average population of P. xylostella larvae in Sekaan Village ranges from 0.98 individuals/plant to 1.82 individuals/plant and the highest average population of P. xylostella larvae in Kedisan Village ranges from 0.7 individuals/plant to 1.66 individuals/plant. The level of parasitization of the parasitoid D. semiclausum in Sekaan Village ranges from 32% to 56% and the level of parasitization of the parasitoid D. semiclausum in Kedisan Village ranges from 24% to 48%. The highest peak of parasitization was found in the fourth observation (4 WAP).